Continuum damage analysis, experimental and simulation for investigating the fatigue life performance of 316L steel at high temperatures. (2017) - Khairul, M.A.; Sapuan, S.M.; AL-Oqla, Faris M.; Zainudin, E.S.; Rababah, M.M.
This work investigates and predicts the fatigue life of 316L stainless steel materials under variable cyclic loading at high elevated temperatures utilising the continuum damage mechanics analysis (CDM). This work is validated experimentally for 316L stainless steel specimens subjected to continuous cyclic loading as well as to hold-time cyclic loading at both room and elevated temperatures where creep plays a significant role. Moreover, this work was carried out in order to examine and investigate the materials' parameters and to obtain improved materials with longer lives. Results obtained from continuous cyclic loading and those exposed to hold-time cyclic loading during the fatigue tests show notable variations in their trend curves. Moreover, this work was capable of developing an approach to predict the fatigue life of such materials at elevated temperatures. A comprehensive understanding of the fatigue behaviour of tubular steel is also developed to enhance safer design possibilities.